ЧЕЛОВЕК В МИРЕ ПЕРМАНЕНТНЫХ КАТАСТРОФ - Вандышев, В. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Автор акцентирует внимание на потребности людей прогнозировать перспективы и особенностидальнейшего развития общества. Особенно острый интерес вызывают те предсказания, которые носятглобальный характер и относятся к сравнительно коротким промежуткам времени. Как всегда, в си-туации гипотетической можно, сославшись на предшествующий опыт, сказать, что эсхатологическиеварианты невозможны, ибо до сих пор всегда были ошибочными. Но изменения грядут, и время их на-стало, а посему следует или смириться с «распадом цивилизации» и угрозами, связанными с развитиемискусственного интеллекта, или энергично прорабатывать пути будущего развитияинтеллект, катастрофизм, смысл истории, технико-информационное общество.Вандишев В.М. Людина в світі катастроф: припущення і реальність. Автор акцентує увагу напотребі людей прогнозувати перспективи і особливості подальшого розвитку суспільства. Особливогострий інтерес викликають ті прогнози, які носять глобальний характер і відносяться до порівнянокоротких проміжків часу. Як завжди, в ситуації гіпотетичній можна, пославшись на попередній досвід,сказати, що есхатологічні варіанти неможливі, бо до цих пір завжди були помилковими. Але зміни на-стають, і час їх настає, а тому слідує або змиритися з «розпадом цивілізації» і погрозами, пов'язаними зрозвитком штучного інтелекту, або енергійно опрацьовувати шляхи майбутнього розвиткуКлючові слова: «вертикаль Панова-Снукса», ноосфера, глобалізація, історія, штучний інтелект,катастрофізм, сенс історії, техніко-інформаційне суспільство.Vandyshev V.N. Man in the world disasters: theory and reality. People have always had the need insome way to forecast the prospects of further development and characteristics of the society. Particularly acuteinterest are the predictions that are global in nature and relate to the relatively short periods of time. To this day,the development of society is increasing in line with financial and technical capacity. As always, in a hypotheticalsituation, it is possible, citing previous experience, to say that the eschatological options are not possible, becauseuntil now have always been wrong. However, changes are coming, and when they arrived, and thereforemust either accept the "collapse of civilization", or vigorously work out the way of the future development.It is impossible not to draw attention to the fact that some scientists believe the destruction of mankind oncomputers. Although the times of Cold War are gone, and the risk of nuclear war has become less likely, but nowthreaten the survival of mankind computers and artificial intelligence. Scientists do not exclude that the script ofthe film "Terminator" can become a reality in the near future.The increasing complexity of computing processes leading to the eventual creation of a single artificial intelligencebelieve Hugh Price and Jaan Tallinn - one of the founders of Skype. A critical moment will come whenthis "universal mind" can create their own computer programs and the technology to re-create their own kind.Keywords: «vertical line of Snuks-Panov», noosphere, globalization, history, informatively-technical society,sense of history, artificial intelligence, catastrophizm.